PERANAN SPIRITUALITAS TERHADAP RESILIENSI PADA MAHASISWA YANG SEDANG MENGERJAKAN SKRIPSI - Yeni Eka Cahyani; Sari Zakiah Akmal (State Islamic University (UIN) Ar-Raniry, 2017)
College students whom arein the process of writing theirfinal papersareexpected to deal with tougher pressures compared to other college students in general, based on both internal and external factors. Internal factors include laziness, low motivation, fear of meeting and difficultiesin adjusting ideas with their paper advisors. Whereas external factors include the minimum time of guidance, difficultiesin finding themes and titles of their papers, along with everything that would come with the writing process. If college students are not able to adjust to the difficulties, conditions such as stress, frustration, and lost of motivation are likely to occur. Therefore, college students whom are in the process of writing final papers may need resilience. Resilience is a personal quality that enablesan individual to rise when dealing with difficulties. Previous research showed that one of the incentive factors of resilience is spirituality.Spirituality is defined as a struggle to achieve goals in the experience of connectedness with the essence of life. The purpose of this research was to find the role of spirituality towards resilience in college students undertaking final paper writing. This research used a quantitative approach and adapted versions of CD-RISC (to measure resilience) and SAIL (to measure spirituality). This research involved 150 samples, obtained using accidental samplingtechnique. Regressionresults showed that spirituality has a significant role towards resilience in college students undertaking final paper writing (12%). This indicates that if college students whom are writing their final paperspossess good levels spirituality that involves connectedness with self, other people or nature as well astranscendent power, it would allow them more capability to deal with difficulties that may occur during their final paper writing process